Targeted Polymeric Nanoparticles as a Strategy for the Treatment of Glioblastoma: A Review - de Paula, Geanne Aparecida; de Paula, Mariana Carlomagno; Paes Dutra, Jessyca Aparecida; Carvalho, Suzana Gonçalves; Di Filippo, Leonardo Delello; Villanova, Janaína Cecília Oliveira; Chorilli, Marlus (Current Drug Delivery, 2025)
Glioblastoma multiforme is the most common and aggressive malignant tumor that affects the central nervous system, with high mortality and low survival. Glioblastoma multiforme treatment includes resection tumor surgery, followed by radiotherapy and chemotherapy adjuvants. However, the drugs used in chemotherapy present some limitations, such as the difficulty of crossing the blood-brain barrier and resisting the cellular mechanisms of drug efflux. The use of polymeric nanoparticles has proven to be an effective alternative to circumvent such limitations, as it allows the exploration of a range of polymeric structures that can be modified in order to control the biodistribution and cytotoxic effect of the drug delivery systems. Nanoparticles are nanometric in size and allow the incorporation of targeting ligands on their surface, favoring the transposition of the blood-brain barrier and the delivery of the drug to specific sites, increasing the selectivity and safety of chemotherapy. The present review has described the characteristics of chitosan, poly(vinyl alcohol), poly(lactic-co-glycolic acid), poly(ethylene glycol), poly(β-amino ester), and poly(ε-caprolactone), which are some of the most commonly used polymers in the manufacture of nanoparticles for the treatment of glioblastoma multiforme. In addition, some of the main targeting ligands used in these nanosystems are presented, such as transferrin, chlorotoxin, albumin, epidermal growth factor, and epidermal growth factor receptor blockers, explored for the active targeting of antiglioblastoma agents.
Keywords: selectivity